Nominal Suffixes in Elemental Movie - Ni Ketut Nadi Oktaviani; I Made Rajeg; Ni Made Ayu Widiastuti (Pusat riset dan Inovasi Nasional, 2025)
Nominal derivational suffixes are important to create new words, making communication more efficient. Nominal derivational suffixes can be found in novel, short story, or even animated movie. Some previous studies have focused only on written media, which limits the exploration of the use of nominal derivational suffixes in spoken language. This study aims to fill this gap by identifying the forms and the functions of nominal derivational suffixes found in the Elemental movie. To collect the data, this study applied documentation method and concordance technique. The data collected were analyzed using a qualitative descriptive method. The data then presented using formal and informal methods. The findings highlighted there were thirty words with nine forms of nominal suffixes. This showed how suffixes contribute to word formation, character speech, and meaning, offering insights for future studies or learners.